Application of omics research in seaweeds with a focus on red seaweeds. (23rd April 2021) - Patwary, Zubaida P; Paul, Nicholas A; Nishitsuji, Koki; Campbell, Alexandra H; Shoguchi, Eiichi; Zhao, Min; Cummins, Scott F
Abstract: Targeted 'omics' research for seaweeds, utilizing various computational and informatics frameworks, has the potential to rapidly develop our understanding of biological processes at the molecular level and contribute to solutions for the most pressing environmental and social issues of our time. Here, a systematic review into the current status of seaweed omics research was undertaken to evaluate the biological diversity of seaweed species investigated (red, green and brown phyla), the levels to which the work was undertaken (from full genome to transcripts, proteins or metabolites) and the field of research to which it has contributed. We report that from 1994 to 2021 the majority of seaweed omics research has been performed on the red seaweeds (45% of total studies), with more than half of these studies based upon two genera Pyropia and Gracilaria . A smaller number of studies examined brown seaweed (key genera Saccharina and Sargassum ) and green seaweed (primarily Ulva ). Overall, seaweed omics research is most highly associated with the field of evolution (46% of total studies), followed by the fields of ecology, natural products and their biosynthesis, omics methodology and seaweed–microbe interactions. Synthesis and specific outcomes derived from omics studies in the red seaweeds are provided. Together, these studies have provided a broad-scale interrogation of seaweeds, facilitating our ability to answer fundamental queries and develop applied outcomes. Crucial to the next steps will be establishing analytical tools and databases that can be more broadly utilized by practitioners and researchers across the globe because of their shared interest in the key seaweed genera.